Trajectory tracking of an oscillating movement with a low-cost IMU in geodetic surveying applications. (May 2021) - Štebe, Gašper; Krapež, Peter; Podobnik, Janez; Kogoj, Dušan
Highlights: Robotic Total Station (RTS) can be used for IMU calibration. Low-cost IMU can be used for 3D tracking of an oscillating object. The Zero-phase filter successfully eliminates the drift of the low-cost IMU. Low-cost IMU significantly improves the RTS kinematic tracking measurement system. Abstract: In this paper, we design a method to use a low-cost IMU (Inertial Measurement Unit) sensor for the absolute positioning of an oscillating object and for improvement of the kinematic RTS (Robotic Total Station) high-precision trajectory tracking accuracy. Typically when using standard methods for position estimation based on IMU measurements, a drift of several hundred meters occurres after only 1 min of operation. When processing IMU measurements with our proposed method, which is based on the Zero-Phase filter (ZPF), the accuracy of the oscillating object's position improved to a few centimeters. We used our method to improve the RTS trajectory tracking system. By combining low-cost IMU and RTS measurements, we were able to obtain highly accurate trajectory at a frequency of IMU measurements. We improved the accuracy of the trajectory tracking compared to linear interpolation between measured RTS samples by 40% and the SNR (Signal-to-Noise Ratio) was more than three times higher.